2011
DOI: 10.1029/2010je003649
|View full text |Cite
|
Sign up to set email alerts
|

Modeling polarimetric radar scattering from the lunar surface: Study on the effect of physical properties of the regolith layer

Abstract: [1] A theoretical model for radar scattering from the lunar regolith using the vector radiative transfer theory for random media has been developed in order to aid in the interpretation of Mini-SAR data from the Chandrayaan-1 and Lunar Reconnaissance Orbiter missions. The lunar regolith is represented as a homogeneous fine-grained layer with rough upper and lower parallel interfaces that possesses embedded inclusions with a different dielectric constant. Our model considers five scattering mechanisms in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 76 publications
4
89
0
Order By: Relevance
“…Initial Clementine bistatic radar observations of the poles were inconclusive that found surface circular polarization ratios that were consistent with an interpretation of water ice in some PSR's, but were later refuted (Nozette et al, 1996;Simpson and Tyler, 1999;Fa et al, 2011). Results from the late 1990's era Lunar Prospector Neutron Spectrometer (LPNS) showed, using image reconstruction techniques applied to epithermal neutron flux maps, that some south polar PSR's had regional signatures of enhanced concentrations of hydrogenous materials (Feldman et al, 1998;Elphic et al, 2007).…”
Section: Introductionmentioning
confidence: 85%
“…Initial Clementine bistatic radar observations of the poles were inconclusive that found surface circular polarization ratios that were consistent with an interpretation of water ice in some PSR's, but were later refuted (Nozette et al, 1996;Simpson and Tyler, 1999;Fa et al, 2011). Results from the late 1990's era Lunar Prospector Neutron Spectrometer (LPNS) showed, using image reconstruction techniques applied to epithermal neutron flux maps, that some south polar PSR's had regional signatures of enhanced concentrations of hydrogenous materials (Feldman et al, 1998;Elphic et al, 2007).…”
Section: Introductionmentioning
confidence: 85%
“…[20] As ice and regolith have similar dielectric properties, it has been suggested that they would be difficult to distinguish in radar returns [Fa et al, 2011]. Such difficulty would ensue even with deposits of relatively pure ice, although this purity factor has not been quantified and the specific amounts of contaminating debris that would erase the high-CPR signature is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Both Earth-and satellite-based radar techniques have since been employed for probing the Moon's surface topography, impact craters morphology, and regolith [2][3][4][5][6][7] . Radar techniques have also been used for finding ice on the Moon 8,9 , although from the view point of radar probing of the Moon this issue continues to remain unresolved 10 . Most of the radar observations for studying the Moon, however, have been made at centimetre wavelength 5 , except for a few which were done from the Earth in the metre-decametre wavelength 2,3,11,12 .…”
mentioning
confidence: 99%
“…On the other hand, Moon echoes have traditionally been used to characterize large phased array VHF atmospheric radars 13,14 , but no attempt has been made to characterize these echoes. Given the fact that surface roughness of the Moon at scales comparable to radar wavelength is one of the important factors that influences radar echoes 10 , characterization of Moon echoes at VHF frequencies assumes significance.…”
mentioning
confidence: 99%
See 1 more Smart Citation